Obrona kultu obrazów w Trzech mowach apologetycznych przeciwko tym, którzy odrzucają święte obrazy św. Jana Damasceńskiego - Feliga, Piotr (Collectanea Theologica, 2018)
St John of Damascus was one of the first theologians who shaped the theology of images. His theology was born in the difficult historical circumstances of the first iconoclasm. This is why it was not always up to the task. But it was John who first defined the image as the object of worship and gave a number of convincing arguments for worshiping them. The basic source of knowledge about the theology of the icon of John of Damascus is his Three Apologetic Treatises against those Decrying the Holy Images. On this basis, I presented the definitions of the cult of images and the various types of worship, then the arguments used by St. John of Damascus in order to validate the worship of images in the context of the Old Testament prohibition on the creation of images and the Christian worship of the saints. Finally, I presented John’s theology as an expression of the Church’s independence from the emperor’s power and his attitude to ecclesiastical tradition, especially to the opinions of the Fathers of the Church.